Exact many-body wave function and properties of trapped bosons in the infinite-particle limit - Cederbaum, Lorenz S. (Physical review, 2017)
The emphasis of this work is on the computation of physical properties as well as of the wave function of interacting bosons in a trap potential. Many-body perturbation theory is employed to study the leading term of these quantities for finite numbers of bosons, and exact solutions are aimed at in the infinite-particle limit. As discussed before, a suitable starting point is the second-quantized Hamiltonian represented in the basis of destruction and creation operators of its own mean-field potential. This choice leads to expressions for the perturbation terms of all quantities which exhibit a very weak dependence on the particle number. Importantly, when applying ideas similar to Bogoliubov's, the Hamiltonian can be reduced in the infinite-particle limit to a much simplified form which is a priori particle-number conserving. The resulting phonon Hamiltonian is diagonalizable by a linear transformation for which an explicit eigenvalue equation is given. Physical properties can be expressed explicitly by elements of this transformation, and of particular relevance is that the particle-number-conserving wave functions of the original many-boson system can be reconstructed using recursion relations. The reconstruction of the particle-conserving wave function from the phonon Hamiltonian can also be used to assess when the infinite-particle limit is reached in practice for finite trapped condensates. Two applications are discussed in detail. For one of them, an exact solution is known which is found, in the infinite-particle limit, to exactly coincide with that of the phonon Hamiltonian. In both examples expressions for the properties are given in closed form. The physics behind the phonon Hamiltonian and its physical properties is discussed.